Rictor amplification promotes NSCLC cell proliferation through formation and activation of mTORC2 at the expense of mTORC1 - Kim, Laura C. (Mol Cancer Res, 2020)
Non-small cell lung cancer (NSCLC) is characterized by genomic alterations, yet a targetable mutation has not been discovered in nearly half of all patients. Recent studies have identified amplification of RICTOR, an mTORC2-specific cofactor, as a novel actionable target in NSCLC. mTORC2 is one of two distinct mTOR complexes to sense environmental cues and regulate a variety of cellular processes including cell growth, proliferation, and metabolism, all of which promote tumorigenesis when aberrantly regulated. Interestingly, other components of mTORC2 are not co-amplified with RICTOR in human lung cancer, raising the question as to whether RICTOR amplification-induced changes are dependent on mTORC2 function. To model RICTOR amplification, we overexpressed Rictor using the Cas9 Synergistic Activator system. Overexpression of Rictor increased mTORC2 integrity and signaling, but at the expense of mTORC1, suggesting that overexpressed Rictor recruits common components away from mTORC1. Additionally, Rictor overexpression increases proliferation and growth of NSCLC 3D cultures and tumors in vivo. Conversely, knockout of RICTOR leads to decreased mTORC2 formation and activity, but increased mTORC1 function. Because Rictor has mTOR-dependent and independent functions, we also knocked out mLST8, a shared mTOR co-factor but is specifically required for mTORC2 function. Inducible loss of mLST8 in RICTOR-amplified NSCLC cells inhibited mTORC2 integrity and signaling, tumor cell proliferation, and tumor growth. Collectively, these data identify a mechanism for Rictor-driven tumor progression and provide further rationale for development of an mTORC2-specific inhibitor.